Descemet membrane endothelial keratoplasty and penetrating keratoplasty in pseudophakic bullous keratopathy: comparison of visual outcomes, graft survival rates, and complications - Tüfekçi Balıkçı, Ayşe; Demir, Nurşah; Burcu, Ayşe; Yalnız Akkaya, Züleyha; Şingar, Evin; Uzman, Selma (The European Research Journal, 2024)
Objective: To compare the outcomes of Descemet Membrane Endothelial Keratoplasty (DMEK) and Penetrating Keratoplasty (PK) in patients with pseudophakic bullous keratopathy (PBK). Methods: Records of 51 eyes of 51 PBK patients (32 male, 19 female) who underwent PK (Group1=38 eyes) and DMEK (Group 2=13 eyes) were reviewed retrospectively. The two groups were compared for Best-corrected visual acuity (BCVA), graft survival rates, and complications. Results: The mean age was 69.1 and 67.1 years in group 1 and group 2, respectively. First-year cumulative survival rates for group 1 and group 2 were 92.1% and 61.5%, respectively, and 89.1% and 51.3% in the second year (P=0.001 by log-rank test). At the last follow-up visit, 2.7% of Group 1 and 30.8% of Group 2 had a BCVA of 0.3 or better (P=0.004). Graft failure was observed in 12 eyes (31.6%) in group 1 and 8 eyes (61.5%) in group 2 (P=0.056). At the last examination, the rates of transparent grafts were 73.7% and 69.2% in group 1 and group 2, respectively (P=0.756). Postoperative glaucoma was observed in 4 eyes (30.8%) in the group 2 and 4 eyes (10.5%) in the group 1 (P=0.083). There was no significant difference between the two groups regarding other complications (P>0.05). Conclusions: DMEK surgery offers a better visual outcome than PK for the treatment of PBK. Careful follow-up of patients is required in terms of glaucoma and graft failure after DMEK. Although the graft survival rate was lower in the DMEK group, a similar rate of graft transparency was achieved at the final examination with repeated DMEK surgery.